The Effect Of Capital Structure And Cash Flow Operations On Profitability In Manufacturing Companies Listed On The Indonesia Stock Exchange - Mutmainnah Yasir; Amir , Amir; Zalkha Soraya (International Journal of Economic Research and Financial Accounting, 2024)
The aim of this research is to determine the influence of capital structure and Cash Flow Operations on profitability in manufacturing companies listed on the Indonesian Stock Exchange. This type of research data is descriptive with a quantitative approach obtained from annual financial report data of manufacturing companies listed on the Indonesian Stock Exchange. The sample used in this research was 30 companies. The data collection used in this research is the documentation method by accessing the idx.Co.id site. The research instrument used in this research uses the panel data method. The results of the research show data using statistical calculations through the Eviews 12 application on the influence of capital structure and Cash Flow Operations on profitability in manufacturing companies listed on the Indonesian stock exchange which was discussed in the previous chapter, so the author draws important conclusions that capital structure research has a positive and significant effect on profitability and cash flow operations have no effect on profitability.